Wireless Communication Using the Platform of Nanotechnology - Laxmi Behera, Bhagya; narayan Mohanty, Mihir (International Journal of Psychosocial Rehabilitation, 2025)
Nanotechnology these days has turned into the most important field of study created and a research field in numerous fields including common, concoction designing, gadgets, and medication, likewise in materials. In the current scenario, nanotechnology is considered as mechanical insurgency which might give more conceivable outcomes and surpass our desires in numerous fields. In media transmission building nanotechnology could give prominent answers for controlled processing, detecting, memory extension, and human-machine connection. Nanotechnology in correspondence models gives the capacity to the inventors to deliver components and sensors that are quite smaller, faster, effective, and not costly for the process of fabrication than their present-day modules. In this paper a review of numerous issues identified with nanotechnology in correspondence models is examined, to study the potential use of different nanotechnology-based improvements in the models and holds potential for future results that may prompt improved correspondence models.